1995
DOI: 10.1161/01.cir.91.11.2717
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Chronic Ventricular Dilation in Patients With End-Stage Cardiomyopathy by Prolonged Mechanical Unloading

Abstract: Chronic hemodynamic unloading of sufficient magnitude and duration can result in reversal of chamber enlargement and normalization of cardiac structure as indexed by the EDPVR, both important aspects of remodeling, even in the most advanced stages of heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
187
0
7

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(199 citation statements)
references
References 22 publications
4
187
0
7
Order By: Relevance
“…Echocardiography reveals decreased left ventricular diameter and an increased ejection fraction [27][28][29]. Among others, we have shown a significant reduction of cardiomyocyte diameters after LVAD).…”
Section: Morphological Changes Of the Myocardium During Chf After Venmentioning
confidence: 93%
“…Echocardiography reveals decreased left ventricular diameter and an increased ejection fraction [27][28][29]. Among others, we have shown a significant reduction of cardiomyocyte diameters after LVAD).…”
Section: Morphological Changes Of the Myocardium During Chf After Venmentioning
confidence: 93%
“…Echocardiographic studies performed in the pre-implant period and at explantation at the time of transplantation in 20 patients, in order to further investigate the effect of unloading on left ventricular function, showed a significant decrease in LV end-diastolic volume, LV end-systolic volume, left atrial volume, and an increase in LV ejection fraction (Thohan et al, 2005). LV pressure-volume relationships were also evaluated in LVAD supported hearts after explantation and a shift towards normal was observed, suggesting that multiple favorable alterations at the cellular, tissue and whole organ level had occurred, described with the general term reverse remodeling (Levin et al, 1995). Although the hearts did not return to completely normal size, an average time of 30.8 days was needed in order for the reverse remodeling to be observed, while at 90 days most of the process was completed in this patient cohort (Madigan et al, 2001).…”
Section: Reverse Remodelingmentioning
confidence: 99%
“…4,5 Importantly, these clinical changes have been attended by concomitant decreases in levels of neurohormones 6,7 and cytokines, 8 suggesting that LVAD support may alter the heart failure "milieu." In an effort to explain these salutary changes in clinical status, investigators have turned to more basic studies and begun to examine myocardial ultrastructure before and after LVAD implantation.…”
Section: See P 2383mentioning
confidence: 99%
“…These latter studies have shown decreased myocyte necrosis 9,10 and apoptosis, 11 decreased myocytolysis, 3 and improved myocyte contractility. 12 The beneficial changes in the biology of the failing myocardium after LVAD support have also been accompanied by favorable changes in the LV chamber geometry, 5 LV wall thickness, 9 and LV volume, 5 as well as a favorable leftward shift in the LV pressure-volume curve. 5 Given the magnitude and multitude of beneficial changes observed within the myocardium after prolonged LVAD support, it is perhaps not surprising that clinical reports have begun to emerge showing that heart failure patients could be weaned successfully from LVAD support.…”
Section: See P 2383mentioning
confidence: 99%